The Effect of Instagram Video on Students’ Speaking Skill in Giving Opinion - Wijipratiwi, Siti; Lolita, Yuri (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
Technology growth in the field of education has resulted in significant changes, particularly in the field of English learning in higher education. Instagram could be one of the alternative instruments for supporting the practice of teaching high school students English as Foreign Language (EFL). Instagram's implementation, which has amassed a large user base over the last decade, could be a valuable teaching tool to aid the learning process. The purpose of this research is to see if using Instagram video as a learning media can help ESL high school students enhance their speaking skills. The subjects of the study consisted of 49 high school students who applied the Cambridge Curriculum. A quasi experimental research design was used in this study. The pre-test and post-test score were obtained by requiring the students to speak monologue giving opinion. Then, the pre-test and post-test data was analyzed by Independent Sample T-test. Based on the test results, significance value (2-tailed) of post-test was .000 lower than .05. Moreover, the researcher found that the post-test mean score of experimental group was 89.92 whereas the control group was 82.71. In short, there was a significant difference in Instagram video usage on senior high school students’ speaking skill. Cohen's d was used to determine the magnitude of the effects, and it showed 2.6. It was discovered that the effects were significant. Thus, the findings suggest that using Instagram video as a learning tool for senior high school students could be beneficial.